2020
DOI: 10.1093/jpepsy/jsaa020
|View full text |Cite
|
Sign up to set email alerts
|

Pathways by which Maternal Factors are Associated With Youth Spina Bifida-Related Responsibility

Abstract: Objective Achieving condition-related autonomy is an important developmental milestone for youth with spina bifida (SB). However, the transfer of condition-related responsibility to these youth can be delayed due to parent factors. This study aimed to investigate two potential pathways by which maternal factors may be associated with condition-related responsibility among youth with SB: (a) Maternal adjustment → perception of child vulnerability (PPCV) → youth condition-related responsibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…In contrast, associations between observed family environment and youth chronic pain were nonsignificant. Other studies have similarly reported different findings for parent-reported versus observed parenting behaviors (Moens et al, 2018), including studies using the current study sample (Driscoll et al, 2020). These findings may also indicate that parent and child perception of family environment may be more salient to the experience of youth chronic pain than is the observed family environment.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast, associations between observed family environment and youth chronic pain were nonsignificant. Other studies have similarly reported different findings for parent-reported versus observed parenting behaviors (Moens et al, 2018), including studies using the current study sample (Driscoll et al, 2020). These findings may also indicate that parent and child perception of family environment may be more salient to the experience of youth chronic pain than is the observed family environment.…”
Section: Discussionmentioning
confidence: 58%
“…The original longitudinal study has been described previously. 9 Of 140 families of children with SB at Time 1, 110 (79%) participated at Time 2, 102 (73%) participated at Time 3 and 93 (66%) participated at Time 4.…”
Section: Resultsmentioning
confidence: 99%
“…This was a secondary analysis of a longitudinal prospective cohort study that has been described elsewhere. 9 In brief, families and youths with SB were recruited from 4 hospitals and a statewide SB association in the Midwest for a longitudinal study of neuropsychological functioning, social relationships and psychosocial adjustment among youths with SB. Inclusion criteria were 1) a diagnosis of SB (myelomeningocele, lipomeningocele or myelocystocele), 2) age 8–15 years, 3) proficiency in English or Spanish, 4) involvement of at least 1 primary caregiver and 5) residence within 300 miles of the laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…Estudos prévios chegaram a achados semelhantes (Butler et al, 2007;Greene et al, 2010). É possível que o instrumento utilizado tenha sido pouco efetivo para evocar relatos de práticas superprotetoras, que são uma tendência importante nas práticas de controle de mães de crianças portadoras de doenças crônicas (Driscoll et al, 2020;Kim et al, 2019). Assim, sugere-se que futuros estudos adotem instrumentos diferentes, sobretudo, medidas observacionais.…”
Section: Discussionunclassified